The effects of abstainer in public government auctions and tenders in the legislation in force in the Kurdistan - Fares, Ruqiya Othman (Journal of Legal and Political Studies, 2024)
The process of selecting a contractor with the administration is a complex process that requires many procedures to begin by submitting bids from all bidders and auctioneers. Therefore, they must commit to maintaining their positive statements issued by them before the administration to conclude the contract. However, sometimes the owner of the winning bid, whether in the tender or the auction, fails to fulfill his obligation to complete the contracting procedures with the administration. Therefore, the abstaining of the bidder and auctioneer to complete the contracting process without a reason is considered a breach of his legal obligation and leads to a set of effects on the abstainer. If the effects are financial, the administration confiscates the initial guarantees submitted by the bidder or auctioneer to the administration at the beginning of the contracting process. This is considered a guarantee of his seriousness in participating in the auction and the tender, and the abstainer includes the difference between the two alternatives. The inclusion of the bidder and auctioneer in the blacklist or deprivation of participation is considered a non-financial effect, within the context of a well-established research plan until the research reaches its conclusion represented in the most prominent conclusions and results or in the proposals and recommendations presented in it in order to fill the deficiencies Defects in the Law on the Sale and Lease of State Property No. 1 of 2021, and the Instructions for Implementing Government Contracts No. 2 of 2016 in the Kurdistan Region - Iraq.
Keywords: Lecturer at Sulaimaniyah University College of Basic Education Division of Mathematics